Converting normal computer screens into 3D displays using parallax barriers - Shivohne Mary Anne Saldanha. (2012)
Due to the growing trend of 3D entertainment and advertising, there has been an increasing interest in 3D TVs and monitors. However, most solutions on the market are quite expensive and can involve additional costs for 3D glasses. The aim of this study is to design an inexpensive, glasses-free 3D display.